Soluções para otimização do tempo decorrente do processo de compras da Universidade Federal de Goiás - Pinto, Edir de Jesus Borges (2024)
Among the requirements imposed by public management in public procurement management, there is a need to implement actions to achieve efficiency and speed in administrative procedures, and consequently, to achieve continuous improvement in the services provided. In this sense, the study aims to build an optimization framework through the Lean Six Sigma methodology to reduce the procurement process time for consumable materials, from the request by the requesting units to the signing of the contract instrument, within the scope of the Federal University of Goiás. For the development of the study, the Lean Six Sigma approach with the application of the DMAIC framework - Define, Measure, Analyze, Improve, and Control was proposed for analysis and improvement suggestions. In this methodology, specific tools are related at each stage of the methodological procedures, including current and future value stream mapping, metrics for the duration of execution of each stage of the procurement process, and the stage for implementing improvements and control. Finally, the study indicated that the Lean Six Sigma methodology, which enabled the prioritization and elimination of causes of inefficiencies in the public procurement process, can help reduce the lead time in the current cycle of procurement processes cycle and optimization of value added in the process